2019
DOI: 10.1002/asia.201900638
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Perfluorooctane Sulfonamide by Acinetobacter Sp. M and Its Extracellular Enzymes

Abstract: The Acinetobacter sp. strain Mi solated from a contaminateds oil sample in Jiangsu Province of China was found to be able to degrade perfluorooctane sulfonamide (PFOSA) effectively.F luoride anion (F À )r eleased from PFOSA degradation was detected by ion chromatography, and showedp ositivec orrelation to the growth curve of Acinetobacter sp. strain M. The PFOSA degradation efficiency of strain Mw as approximately 27 %, as assessed by GC analysis. It was shown that enzymes localized outside of cellso fAcinetob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…LUNF3 enriches the resources of PAE-degrading bacteria. The genus Acinetobacter can also eliminate other pollutants, such as sulfamethoxazole [ 32 ], perfluorooctane sulfonamide [ 33 ], crude oil [ 34 ] and phenol [ 35 ]. Therefore, they have a potential application in the remediation of contaminated environments.…”
Section: Resultsmentioning
confidence: 99%
“…LUNF3 enriches the resources of PAE-degrading bacteria. The genus Acinetobacter can also eliminate other pollutants, such as sulfamethoxazole [ 32 ], perfluorooctane sulfonamide [ 33 ], crude oil [ 34 ] and phenol [ 35 ]. Therefore, they have a potential application in the remediation of contaminated environments.…”
Section: Resultsmentioning
confidence: 99%
“…Acinetobacter is a common bacteria in soil. It has been found that Acinetobacter can degrade the sulfur and phosphorus of pesticides, which can repair soil polluted by pesticides, and some species have degradation functions [ 56 ]. In our study, we found that the abundance of Acinetobacter species decreased after AITC fumigation, which may be related to their short life cycles [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In different soil layers, with the application of atrazine, the abundance of Nitrospira , Pseudomonas , Sulfuricurvum , Acinetobacter , Flavobacterium , Salinibacterium , and Pedobacter in AT groups increased significantly compared with CK groups. These bacteria play an important role in the degradation of pesticides [ 43 ], heavy metals [ 44 ], lignin [ 45 ], perfluorooctane sulfonic acid [ 46 ], polycyclic aromatic hydrocarbons [ 47 ], polychlorinated biphenyls [ 48 ], and cellulose [ 49 ], which may be the reason for the increase in abundance of these bacteria after atrazine application for a period of time.…”
Section: Discussionmentioning
confidence: 99%